Influence of Knowledge Sharing on Teacher Performance through Individual Innovation Capability: A Study at PPTQ Darul Fikri Sidoarjo - Nur Bayani Anggit; Gendut Sukarno (Indonesian Journal of Business Analytics, 2023)
The objective of this study is to assess the influence of knowledge sharing on employee performance via individual innovation capabilities at PPTQ Darul Fikri Sidoarjo. The research encompasses teachers from both junior high school (SMP) and senior high school (MA) levels as the target population. The sampling method utilized is non-probability sampling with a purposive approach, resulting in a total sample size of 65 respondents. The dataset comprises two types: primary data, acquired from respondent responses to questionnaires, and secondary data, sourced from PPTQ Darul Fikri Sidoarjo. Data analysis is conducted employing the Partial Least Squares (PLS) technique. The research outcomes disclose a favorable effect of knowledge sharing on employee performance through individual innovation capabilities within the context of PPTQ Darul Fikri Sidoarjo.